2022
DOI: 10.1021/acsnano.2c09036
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Mo, W-Conjugated Polarization, and Oxygen Vacancies of MoO2/WO3 in Enhanced Microwave Therapy for MRSA-Induced Osteomyelitis

Abstract: Deep tissue infection, such as osteomyelitis, caused by methicillin-resistant Staphylococcus aureus (MRSA) infection, poses a serious threat to public health and cannot be effectively treated by antibiotics. In this study, we report a microwave (MW)-responsive MoO 2 /WO 3 heterojunction that can be utilized to effectively treat MRSA-infected osteomyelitis under MW irradiation because of the enhanced MW thermal effect and MW catalysis of the composite. The underlying mechanism is as follows: A myriad of oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…5a, it can be seen that the total DOS of N-PC@IC/Co/rGO was mainly occupied by Co, and the metallic conductivity was proved by the electronic state occupying the Fermi surface. 28 Simultaneously, the outstanding conductivity could be demonstrated by the high delocalization near the Fermi level, 25 which corresponded to the conductivity results. To further explore the electronic migration, the work function was utilized (Fig.…”
Section: Resultssupporting
confidence: 71%
“…5a, it can be seen that the total DOS of N-PC@IC/Co/rGO was mainly occupied by Co, and the metallic conductivity was proved by the electronic state occupying the Fermi surface. 28 Simultaneously, the outstanding conductivity could be demonstrated by the high delocalization near the Fermi level, 25 which corresponded to the conductivity results. To further explore the electronic migration, the work function was utilized (Fig.…”
Section: Resultssupporting
confidence: 71%
“…47 DCFH could be then oxidized to fluorescing 2′,7′-dichlorofluorescein (DCF) by ROS, and the fluorescence intensity of DCF can directly reflect the oxidative stress. 48 The MRSA cells in the LS-Ti 3 C 2 group showed the highest fluorescence intensity (Figure 5G galactopyranoside (ONPG) intensity of the LS-Ti 3 C 2 group was the highest among the groups (Figure 5H), 49 which indicated that US-triggered ROS in the LS-Ti 3 C 2 group led to the enhancement of bacterial membrane permeability. Also, the LS-Ti 3 C 2 nanosheets caused enhancement of protein leakage and significant reduction of adenosine triphosphate (ATP) activity of MRSA owing to highly efficient SDT (Figure 5I,J).…”
Section: Resultsmentioning
confidence: 93%
“…Subsequently, 2′,7′-dichlorodihydrofluorescein diacetate (DCFH-DA) was applied to discover intracellular ROS, which is hydrolyzed into dichlorofluorescin (DCFH) after it enters the bacteria . DCFH could be then oxidized to fluorescing 2′,7′-dichlorofluorescein (DCF) by ROS, and the fluorescence intensity of DCF can directly reflect the oxidative stress . The MRSA cells in the LS-Ti 3 C 2 group showed the highest fluorescence intensity (Figure G and Figure S13), indicating that the US-triggered extraordinary ROS release caused fatal oxidative stress to the MRSA bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…All the samples have more than one semicircle, suggesting that multiple dielectric relaxation is present, contributing to the dielectric loss, which is consistent with peaks observed in the real and imaginary parts of complex permittivity. The presence of defects and oxygen vacancies also leads to the accumulation of charges at the interfaces of grain boundaries, causing interfacial polarization and dielectric relaxation, which can also enhance the dielectric loss of the materials [66]. Furthermore, a partial linear behaviour is noticed between ϵ ′ (ω) and ϵ ′ ′ (ω) for all the samples.…”
Section: Em Loss Propertiesmentioning
confidence: 93%